1991
DOI: 10.1002/ijc.2910490115
|View full text |Cite
|
Sign up to set email alerts
|

Severe cachexia in mice inoculated with interferon‐γ‐producing tumor cells

Abstract: Nude mice were inoculated with CHO/IFN-gamma cells, a line of Chinese hamster ovary tumor cells, that had been genetically engineered to produce murine IFN-gamma. Severe cachexia, as evident from body weight loss and reduced food intake, occurred in these mice, but not in those injected with CHO/control cells, i.e. the original, non-IFN-gamma-producing line. The essential role of IFN-gamma in the pathogenesis of cachexia was confirmed by the demonstration that monoclonal antibodies (MAbs) against IFN-gamma, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 23 publications
0
79
0
2
Order By: Relevance
“…Given these inhibitory effects, TGF-β1 deficiency might perturb normal immune and inflammatory system homeostasis, resulting in unregulated activity that is fatal to the organism. For example, dysregulated production of interferon-γ and TNF-α by activated T cells and macrophages, respectively, could contribute to the mutant phenotype as both cytokines mediate weight loss and inflammation 29,30 . The involvement of interferon-γ and TNF-α are consistent with the observed elevation of these cytokines in the mutant animals.…”
Section: Discussionmentioning
confidence: 99%
“…Given these inhibitory effects, TGF-β1 deficiency might perturb normal immune and inflammatory system homeostasis, resulting in unregulated activity that is fatal to the organism. For example, dysregulated production of interferon-γ and TNF-α by activated T cells and macrophages, respectively, could contribute to the mutant phenotype as both cytokines mediate weight loss and inflammation 29,30 . The involvement of interferon-γ and TNF-α are consistent with the observed elevation of these cytokines in the mutant animals.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have described the contribution of cytokines and adhesion molecules in the development and/or progression of cancer and/or cachexia. [4][5][6][7][8] Recent advances in molecular biology provide us with the opportunity to dissect out this complicated disease. Numerous growth factors and cytokines including IL-1, IL-6, IL-8 and TNF-␣, to name a few, regulate this process.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Although little is known about the precise mechanism of cachexia, recent studies indicate that inappropriate production and release of cytokines such as tumor necrosis factor-␣ (TNF-␣), interleukin-1 (IL-1), interleukin-6 (IL-6) and interferon-␥, which are secreted from both cancer cells and host tissues, are involved in the induction of cachexia. [4][5][6][7][8] These cytokines have been pos-tulated to cause metabolic changes in the host, associated with enhanced energy requirements for tumor growth, resulting in the loss of adipose and muscle tissues. Blockade of the cytokines by their antibodies reversed the body weight loss and tissue wasting without affecting tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Cachexia is known to be caused by mediators produced by tumours or by the host as a result of tumour-host interaction. Previously, various factors have been proposed as cachexia mediators, such as tumour necrosis factor alpha (TNF-α) (Oliff et al, 1987;Tracey et al, 1988;Stovroff et al, 1988;Yoneda et al, 1991), interferon gamma (IFN-γ) (Matthys et al, 1991a(Matthys et al, , 1991b, interleukin (IL)-1α (Moldawer et al, 1987;Gelin et al, 1991), leukaemia inhibitory factor (LIF) (Mori et al, 1991) and IL-6 (Yoneda et al, 1993;Tamura et al, 1995). Fujimoto-Ouchi et al (1995) and Strassmann et al (1992a) reported that anti-IL-6 antibody suppressed the progressive body weight loss and other disorders associated with cachexia in mice bearing colon 26.…”
mentioning
confidence: 99%